2003
DOI: 10.1038/ni1018
|View full text |Cite
|
Sign up to set email alerts
|

Commensal anaerobic gut bacteria attenuate inflammation by regulating nuclear-cytoplasmic shuttling of PPAR-γ and RelA

Abstract: The human gut microflora is important in regulating host inflammatory responses and in maintaining immune homeostasis. The cellular and molecular bases of these actions are unknown. Here we describe a unique anti-inflammatory mechanism, activated by nonpathogenic bacteria, that selectively antagonizes transcription factor NF-kappaB. Bacteroides thetaiotaomicron targets transcriptionally active NF-kappaB subunit RelA, enhancing its nuclear export through a mechanism independent of nuclear export receptor Crm-1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
655
5
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 916 publications
(679 citation statements)
references
References 42 publications
13
655
5
6
Order By: Relevance
“…Two different paradigms have been proposed to explain the apparent inertia of mucosal surfaces to the [12,13]. It is unclear, however, which receptors are engaged, how TLR4 is involved, which adaptors are recruited, and how the reduction in NF-jB comes about.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Two different paradigms have been proposed to explain the apparent inertia of mucosal surfaces to the [12,13]. It is unclear, however, which receptors are engaged, how TLR4 is involved, which adaptors are recruited, and how the reduction in NF-jB comes about.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies of gut epithelial cells have suggested that commensals actively inhibit the epithelial response by disrupting NF-jB-dependent transcription mechanisms [12,13]. It is unclear, however, which receptors are engaged, how TLR4 is involved, which adaptors are recruited, and how the reduction in NF-jB comes about.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently Neish et al (2000) demonstrated that avirulent Salmonella abrogates production of inflammatory cascade by inhibiting ubiquitination and degradation of IkB, thus blocking the transactivation of NFkB-mediated genes. More recently, Kelly et al (2004) identified an interesting mechanism by which commensal flora may regulate host inflammatory responses and maintain immune homeostasis, by promoting nuclear export of NFkB subunit relA, through a PPAR-γ-dependent pathway. Similarly, Rakoff-Nahoum et al (2004) demonstrated that recognition of commensal microflora by Toll-like receptors is required for intestinal homeostasis, explaining why disequilibrium in this signalling pathway can lead to the initiation of inflammatory bowel diseases.…”
Section: Ii2d : Signals From Peripheral Endocrine Factorsmentioning
confidence: 99%